A Gender Based Analysis of Emotional Intelligence and Job Performance of Teachers at Higher Secondary School Level - Gul, Farah; Zamir, Shazia (University of Wah Journal of Social Sciences, 2021)
The present study was aimed to study the Gender based Analysis of EI and performance of teachers on job at higher secondary school level. The nature of this study was descriptive and data was gathered by survey method. There were 90male teachers and 115 female teachers were carefully chosen from the Islamabad Model higher secondary schools by means of stratified random sampling technique. A standardized questionnaire for measuring: ―Emotional Intelligence‖ the assessment of emotional intelligence scale by Schutte was used with four sub scales and ―Teacher job performance‖ job satisfaction scale by Ching et al., 2016 with five sub scale was used. A data set was created through Statistical Package for Social Sciences (SPSS). Mean, SD and frequencies are used for statistical analysis of the data along with independent t test. Management of self has shown the higher mean score as compared to the other sub scales of Emotional Intelligence. Similarly, the mean value of working Environment is greater than the mean values of other all dimensions of job performance scale. Results indicated that there is a substantial difference in EI and performance of job by female and male teachers at secondary high school. There is no significant difference found with respect to Management of self in Emotional Intelligence scale and Working environment in job performance scale. It may be recommended that the teachers with high Emotional Intelligence will perform well in their organization which will be resulted as the improvement in their job performance.